Post-harvest useful life of ‘Prata’ bananas stored under refrigeration (Research, Society and Development, 2021)
Banana is climacteric fruit and therefore needs adequate refrigerated storage. Aimed evaluate the post-harvest useful life of ‘Prata’ bananas stored under refrigeration. The fruits were stored in a cold chamber, during 15 days at 13 ± 4 ºC (85 ± 4% U.R.) followed by 8 days at 22 ± 4 ºC (85 ± 4% U.R.). A completely randomized design was used in a 3 x 8 factorial scheme, the first factor being (Prata Anã, Prata Catarina and Prata Rio) and the second the times (0, 5, 10, 15, 17, 19, 21 and 23) days. At each time analized: mass loss, skin color, external appearance, pulp firmness, skin thickness, pulp diameter, pH, titratable acidity (TA), soluble solids (SS), soluble solids and titratable acidity ratio SS / TA, and total soluble sugars were analyzed. Descriptive statistic were used by applying the mean and standard deviation from tree replication of tree fruits per plot. The fruits of the Prata Catarina genotype showed less weight loss and better external appearance on the 21st day of storage. The Prara Anã and Prata Catarina genotypes showed slower and more accelerated metabolism, respectively at 13 ºC, as they showed different physiological behavior in terms of skin color, pulp firmness, titratable acidity, soluble solids and total soluble sugars. Based on the external appearance, the post-harvest useful life of the fruits of the Prata Anã and Prata Rio genotypes was 19 days (15 days at 13 ºC and 4 days at 22 ºC), while that of the fruits of the Prata Catarina genotype was 21 days (15 days at 13 ºC and 6 days at 22 ºC).